2014
DOI: 10.5312/wjo.v5.i3.262
|View full text |Cite
|
Sign up to set email alerts
|

Scoring system for prediction of metastatic spine tumor prognosis

Abstract: Assessing the prognosis before treatment for metastatic spine tumor is extremely important in therapy selection. Therefore, we review some prognostic scoring systems and their outcomes. Articles with combinations of two keywords among "metastatic spine tumor" and "prognosis", "score", "scoring system", "predicting", or "life expectancy" were searched for in PubMed. As a result, 236 articles were extracted. Those referring to representative scoring systems about predicting the survival of patients with metastat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
98
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 139 publications
(110 citation statements)
references
References 64 publications
0
98
0
4
Order By: Relevance
“…Poor survival after spinal surgery for lung metastases previously reported by Weiss and Wedin. 12,13 Those with breast disease fared significantly better giving a true reflection of the value of the intervention in those with metastatic spinal disease from breast cancer. A relative strength in this study is the selection of true metastatic disease.…”
Section: Discussionmentioning
confidence: 99%
“…Poor survival after spinal surgery for lung metastases previously reported by Weiss and Wedin. 12,13 Those with breast disease fared significantly better giving a true reflection of the value of the intervention in those with metastatic spinal disease from breast cancer. A relative strength in this study is the selection of true metastatic disease.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, they had no factors of therapeutic intervention, and the criteria were relatively flexible and versatile. Therefore, they have been evaluated by replication studies worldwide including our studies 15,16) , and relatively favorable results have been reported 2,[17][18][19] . These papers were the first reports on scoring systems for the prognosis of metastatic spine tumors and have long been landmark articles concerning the prognosis after the revision in 2005 14) .…”
Section: Scoring System For Predicting Life Expectancy 1) Classicmentioning
confidence: 99%
“…It was simplified by excluding paralysis, which was not considered to affect the life prognosis. In addition, expected survival period and treatment selection including the indication for conservative therapy were specified in detail according to the total score: An expected survival period of 2 years or longer and en bloc excision for scores of 2-4, 1-2 years and debulking for scores of 4-6, 6-12 months and palliative decompression for scores of 6-8, and 3 months or less and terminal care for scores of 8-10. This scoring system, prepared in a surgical patientcentered manner, is often used for the evaluation of surgical indications along with the Tokuhashi score, and its usefulness has been evaluated in many reports 2,[33][34][35][36][37][38][39][40] . Baur HCF (2002) 41) considered that this scoring system succeeded in the differentiation between poor and good prognosis groups but suggested underestimation of pain and paralysis, lack of specificity for urgent paralysis, and overemphasis of aggressive surgical treatments with understatement of indications for conservative therapy and palliative surgery.…”
Section: Scoring System For Predicting Life Expectancy 1) Classicmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, patients with primary or benign spinal column tumors often experience prolonged survival, 17 which warrants the need for arthrodesis, although complications such as kyphosis, device subsidence, device loosening, or device fracture may be encountered. 2,4,15,46 In contrast, because patients harboring metastatic spinal column tumors or malignant tumors not amenable to en bloc resection may have relatively limited life expectancy, depending on factors such as tumor histology, extraspinal metastases, and performance status, 64 achievement of fusion may not be required. 21,54 Lastly, there are some limitations in bone graft options in spinal oncology.…”
mentioning
confidence: 99%